2007
DOI: 10.1002/jpln.200625051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phosphorus application on growth and cadmium uptake of spinach in two cadmium‐contaminated soils

Abstract: A pot experiment was conducted to investigate the influence of phosphate (P) application on diethylene triamine pentaacetic acid (DTPA)–extractable cadmium (Cd) in soil and on growth and uptake of Cd by spinach (Spinacia oleracea L.). Two soils varying in texture were contaminated by application of five levels of Cd (NO3)2 (0, 20, 30, 40, and 60 mg Cd kg–1). Three levels of KH2PO4 (0, 12, and 24 mg P kg–1) were applied to determine immobilization of Cd by P. Spinach was grown for 60 d after seeding. Progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(22 citation statements)
references
References 19 publications
2
20
0
Order By: Relevance
“…7). Similar results have also been reported (Keller and Römer, 2001;Zhang et al, 2002;Dheri et al, 2007). Application of P-containing materials influences the bioavailability of heavy metals such as Cd, Pb, and Zn in soil (Qiu et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…7). Similar results have also been reported (Keller and Römer, 2001;Zhang et al, 2002;Dheri et al, 2007). Application of P-containing materials influences the bioavailability of heavy metals such as Cd, Pb, and Zn in soil (Qiu et al, 2011).…”
Section: Discussionsupporting
confidence: 87%
“…The presence of 100 µM Cd didn't affect root length of lettuces after 7 days of culture in Hoagland's medium enriched with Cd(NO 3 ) 2 [11]. When phosphorus was added at 686 mg/L level, root length was inhibited only when cadmium was at its highest level (0.372 mg/L) and this behavior was not observed when P2 was applied enhancing the hypothesis of Cd-P complex formation in roots that inhibits cadmium absorption [4] (Table 5). Although in non-significant way, root length was increased when P was added as it is a limiting factor for plant and root growth.…”
Section: Root Part Of Lactuca Sativa Grown Under Cadmium Treatmentsmentioning
confidence: 93%
“…It is considered as a potentially phytotoxic element due to its high toxicity and solubility in water [4]. Most general symptoms of Cd toxicity in plants are stunted growth, chlorosis, necrotic lesions, wilting and disturbances in mineral nutrition and carbohydrate metabolism.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an adequate and balanced supply of nutrients at the correct time is required for the proper growth and development of plants, maintenance of better soil fertility, and preservation of an intensive cropping system to maintain the global food production, particularly in developing countries (Dordas, 2009;Hansch and Mendel, 2009;Sarwar et al, 2010;Moharana et al, 2012;Waraich et al, 2012). In addition, studies also showed that an exogenous supply of nutrients plays a crucial role in the enhancement of plant tolerance against various abiotic stresses (Pankovic et al, 2000;Hassan et al, 2005;Tlustos et al, 2006;Dheri et al, 2007;Sarwar et al, 2010). Some Abbreviations: DMAS, deoxymugineic acid synthase; FRO, ferric-chelate reductase oxidase; HA, H + -ATPase; IRT, iron-regulated transporter; MAs, mugineic acid family phytosiderophores; NA, nicotianamine; NAAT, nicotianamine aminotransferase; NAS, nicotianamine synthase; PEZ, PHENOLICS EFFLUX ZERO; SAM, S-adenosyl-L-methionine; TOM1, transporter of mugineic acid family phytosiderophores 1; YS1/YSL, YELLOW STRIPE 1/YELLOW STRIPE 1-like.…”
Section: Introductionmentioning
confidence: 99%